Choir Art in Uzbekistan Botir Umidjanov - Muyassarkhon Achildiyeva; Farangiz Ikramova (Genius Journals, 2022)
This article discusses the role of choral art in the life of people in Uzbekistan and the history of its development. At the same time, the musical heritage of Botir Umidjanov, who made a significant contribution to the art of choir, is reflected
Keywords: Chorus; sapella; ensemble; tradition